Specificity and promiscuity of phosphoinositide lipid interactions with the serotonin1A receptor: insights from submillisecond coarse-grain simulations - Nikte, Siddhanta V.; Sengupta, Durba; Chattopadhyay, Amitabha (ACS Chemical Neuroscience, 2026)
G protein-coupled receptors (GPCRs) are lipid-dependent membrane receptors that serve as important cell signaling hubs. Phosphoinositide (PIP) lipids represent an important class of anionic lipids that play vital roles in neuronal function and signaling. PIP lipids have been reported to modulate GPCR function, although the specificity and molecular details of the interactions are still not clear. An important GPCR in this context is the serotonin(1A) receptor, a neurotransmitter GPCR, which has been reported to interact with phosphatidylinositol 4-phosphate (PIP1) lipids. In this work, we computationally analyzed the specificity of the serotonin(1A) receptor-PIP lipid interactions using coarse-grain molecular dynamics simulations. Our results predict that four anionic lipid sites are present at the receptor surface, although the relative populations are dependent on the lipid type. PIP1 lipids exhibit the highest interaction at a charged cleft formed by transmembrane helices VI and VII. We observed electrostatic interactions at a cluster of charged residues (Arg341, Lys342, Lys345) and hydrophobic and aromatic interactions at residue Ile349 and Tyr402. In contrast, phosphatidylinositol 4,5-bisphosphate (PIP2) and phosphatidylinositol 3,4,5-trisphosphate (PIP3) lipids interact more with transmembrane helix IV. We observed that anionic phospholipids such as phosphatidylserine (PS) interact at these sites, although their occupancy at these sites is much reduced. By elucidating the molecular determinants of these interactions in silico, this study generates novel, testable hypotheses regarding the functional role of specific lipid-receptor contacts. Our work constitutes an important step in analyzing molecular signatures of phosphoinositide lipid-GPCR interactions in the overall context of diverse roles of phosphoinositides in neuronal function and signaling.
Keywords: anionic lipids; Cholesterol; GPCR; MARTINIcoarse-grain simulations; PIP lipids; serotonin(1A) receptor